Una especie nueva de Plinia l. (Myrtaceae) del Caribe sur de Costa Rica - Gómez-Laurito, Jorge; Valverde, Oscar (Lankesteriana: International Journal on Orchidology, 2016)
A new species of Plinia L. (Myrtaceae) with conspicuosly cuspidate leaves, small flowers and oblate, asymmetric, smooth, and strongly compressed fruits is described from the southern Caribbean region of Costa Rica.